2010
DOI: 10.2188/jea.je20090053
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Incidence of Cardiovascular Events in a Japanese Population: The Jichi Medical School Cohort Study

Abstract: BackgroundAlthough sleep is one of the most important health-related factors, the relationship between sleep duration and the incidence of cardiovascular events has not been fully described.MethodsThe present study comprised the 11 367 study subjects (4413 men and 6954 women) of the Jichi Medical School Cohort Study, a population-based prospective study. Baseline data were obtained by questionnaire and health examinations between April 1992 and July 1995 in 12 rural areas in Japan, and the main outcome measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
88
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 21 publications
6
88
2
Order By: Relevance
“…Spline analysis using linear models did not shown any difference in events with shorter duration than 7 hours for both cardiovascular mortality (8 studies)11, 25, 44, 47, 49, 71, 87, 88 and CVD (7 studies) 8, 12, 22, 33, 38, 42, 74. However, longer self‐reported sleep duration >7 hours appeared to be associated with a moderate increase in greater stroke mortality (cubic model shown in Data S8).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Spline analysis using linear models did not shown any difference in events with shorter duration than 7 hours for both cardiovascular mortality (8 studies)11, 25, 44, 47, 49, 71, 87, 88 and CVD (7 studies) 8, 12, 22, 33, 38, 42, 74. However, longer self‐reported sleep duration >7 hours appeared to be associated with a moderate increase in greater stroke mortality (cubic model shown in Data S8).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 74 studies met the inclusion criteria; the process of study selection is shown in Figure 1 8, 9, 11, 12, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89,...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also verified that lack of students causes various disorders, causes the risk of the occurrence of various disorders in autonomic nerve activity [30] [31], the endocrine system [32]- [37] and the cardiovascular system [38]- [43]. Therefore, in order to prevent diseases in the future, it is important to acquire a desirable life rhythm and maintain enough students from a very young age.…”
Section: Resultsmentioning
confidence: 99%